Electrochemical Fabrication of Gold Quantum Wire with Atomic-Scale - Dong, Xiaodong; Liu, Junhua (Asian Journal of Chemistry, 2012)
Stable gold quantum wire with atomic-scale was successfully fabricated with two kinds of electrochemical method in solution by a home-made electrochemically controlled system. The quantum wire could be obtained by careful controlling the process of electrochemical deposition on a preformed gold electrode pair as well as its reverse process-etching with addition of chloroauric acid in solution. The stepwise conductance behaviour could be observed clearly with the process. Another method was a self-terminated electrochemical mechanism. Compared with the first method, it was simpler, less interferential and more suitable for in situ study of quantum wire. The I-V curve of the formed gold quantum wire showed the ohmic behaviour with low bias voltage and electromigration phenomenon with high bias voltage.